Application and prospects of ultrasound combined with immunotherapy in cancer treatment of intensive care - Wang, Yaping; Liu, Cong; Lyu, Riley; Zhang, Yan (Frontiers in Immunology, 2025)
The tumor microenvironment (TME) plays a crucial role in tumor initiation, progression, and metastasis, and immunotherapy targeting the TME has received increasing attention. However, single-agent immunotherapy has certain limitations and often requires combination with other adjuvant strategies to enhance therapeutic efficacy. Among these, ultrasound has emerged as a promising adjunct to cancer immunotherapy. By modulating the TME, ultrasound combined with immunotherapy shows great potential in enhancing antitumor responses. This review summarizes the application of various ultrasound modalities in enhancing antitumor immunity, improving the efficacy of immunotherapy, and regulating the TME. Ultrasound can amplify the therapeutic effects of immunotherapy through multiple mechanisms, including thermal effects, mechanical effects, microbubble cavitation, and sonodynamic therapy. Thermal effects induced by high-intensity focused ultrasound (HIFU) can destroy tumor tissues, releasing tumor antigens and heat shock proteins, thereby activating systemic immune responses. Mechanical approaches such as histotripsy can liquefy tumors without thermal damage, preserving antigenic structures and enhancing immune responses within the TME. Ultrasound-mediated microbubble cavitation increases vascular permeability, facilitating the delivery of immune cells and immune checkpoint inhibitors into tumor tissues and enhancing signal transduction to convert “cold” tumors into immune-active “hot” tumors. Sonodynamic therapy generates reactive oxygen species under ultrasound stimulation, inducing immunogenic cell death and reshaping the TME. Furthermore, this review outlines the research progress of ultrasound-immunotherapy combinations in various cancers, including lung cancer, breast cancer, and melanoma, demonstrating superior efficacy compared to immunotherapy alone. Ultrasound not only enhances antitumor immune effects but also enables real-time monitoring of tumor progression and immune modulation within the TME. Finally, the review discusses current challenges and future prospects. By systematically summarizing the types of ultrasound-assisted immunotherapy, their mechanisms within the TME, and recent advances in clinical applications, this article aims to provide a theoretical foundation and technical reference for developing ultrasound-immunotherapy strategies targeting the TME.